El origen del hombre - Piddington, Andrew; Ashton, Paul D.M.; Theunissen, Amanda; Glover, Danny; Granada Productions; Discovery Channel (Firma); Libra Films (Firma); Artisan Home Entertainment (Firma); Family Home Entertainment (Firma) (Bethesda, Md. : distributed by Discovery Channel ; Santa Monica, CA : Artisan Home Entertainment : Family Home Entertainment, 2002)
Usando la última reconstrucción del ADN y con la tecnología de vanguardia, los científicos investigan la ubicación de la primera mujer de la raza human.
Directors of photography, Brian Apps, Roger Eaton, Paul Williams ; editor, Tony Palmer ; music, Mark Thomas.
Narrated by Danny Glover.
MPAA rating: Not rated.
DVD, Region 1 encoding, digitally mastered.
Diálogos en inglés y español.
Keywords: Genética de población humana; Evolución humana; Antropología prehistórica; Cine documental; Programas documentales de televisión; América -- Antiguedades